The impact of training and development management practices on organization performance at UNIKL business school / Siti Najwa Abdul Rahman - Abdul Rahman, Siti Najwa (Faculty of Business and Management, 2018)
Achieving some standard of performance is the objective of all organizations because through these performances, organizations are able to grow and progress. Over the past twenty years, the field of training and development management practices has progressed to become the backbone of today’s human resource practices. The purpose of this study is to investigate the impact of training and development management practices on organizational performance and to determine the direction of the effect as well as the most influential training and development management practices towards the organizational performance within UniKL Business School. This study is a quantitative research which had used the self-administered electronic questionnaire as instrument for the collection of data. The data was collected and viable out of possible 44 respondents which derive from the total population of 50 respondents. Sample selection was based on simple random sampling method. The data collected was then evaluated by using Statistical Package Social Science (SPSS) Version 20 Software. Using SPSS, numerous tests were converged such as Reliability Analysis, Frequency Distribution, Descriptive Analysis, Pearson’s Correlation Analysis and Multiple Regression. The results indicated that training and development management practices which include Organization Learning, Training Need Analysis and Training Formalization are related to Organizational Performance.